Disordered eating among adolescents with chronic pain: the experience of a pediatric rheumatology subspecialty pain clinic - Lauren Pianucci; Maitry Sonagra; Brooke A. Greenberg; Diana R. Priestley; Sabrina Gmuca (Pediatric Rheumatology Online Journal, 2021)
Abstract Background Disordered eating and chronic pain often co-occur in adolescents, but the relationship between these conditions is not well understood. We aimed to determine the prevalence of and to identify the clinical characteristics associated with the presence of disordered eating among adolescents with chronic musculoskeletal pain (CMP) presenting to a pediatric rheumatology subspecialty pain clinic. Methods This was a retrospective cohort study of pediatric patients presenting to a pediatric rheumatology subspecialty pain clinic for an initial consultation from March 2018 to March 2019. We complemented data from an existing patient registry with secondary chart review for patients identified with disordered eating. We compared patient characteristics based on the presence or absence of disordered eating among adolescents with CMP. Logistic regression modeling was used to determine factors associated with disordered eating. Results Of the 228 patients who were seen for an initial consultation in the pain clinic in 1 year, 51 (22.4%) had disordered eating. Only eight (15.7%) of the 51 patients identified with disordered eating had a previously documented formal eating disorder diagnosis. Through multivariate logistic regression modeling, we found that disordered eating was associated with older age, higher functional disability, presence of abdominal pain, presence of gastrointestinal comorbidities, and presence of anxiety (all p < 0.05). Conclusions Adolescents with chronic pain, especially those who experience gastrointestinal issues, anxiety, and greater functional disability, should be evaluated for disordered eating by the treating clinician in order to ensure timely and appropriate treatment.